Зображення нелінійностей в скінченновимірних гіперкомплексних числових системах - Синьков, М.В.; Каліновський, Я.О.; Боярінова, Ю.Є.; Федоренко, О.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Construction of the representations of nonlinear functions in hypercomplex numerical systems is of great importance. Here, methods for construction of representations for direct and inverse nonlinear functions in finite-dimensional hypercomplex numerical systems are considered. Examples of the constructed representations for nonlinearities in some hypercomplex numerical systems are listed.